Undang-undang penguatkuasaan fatwa di Malaysia - Zaini Nasohah (Penerbit Universiti Kebangsaan Malaysia, 2005)
The states Administration of Islamic Law Act, Enactment and Ordinance provide that, no statement made by the Mufti shall be taken as a Fatwa unless and until it is ruling according to the enacted procedures and then published in the Gazette. Since the jurisdiction of the administration of Islamic Law has been given to the states, the enforcement of the fatwa is under the state jurisdiction. Beside that, no state can be forced to recognize the Fatwa made by the National Fatwa Council. This article elaborates some problems relating to the Fatwa in Malaysia expecially with regard to its enforcement